INFLUENCE OF WATER TEMPERATURE AND SALINITY ON pH DURING DRY SEASON IN LOWER DONG NAI RIVER SYSTEM, VIETNAM - Dung, Dang Quoc (GeoScience Engineering, 2016)
This paper uses gvSIG 2.2.0 software, IDW interpolation method, river and stream network data, and 36 sampling locations to build the maps in dry season of three monitored parameters pH, water temperature, and salinity in Lower Dong Nai River system (2009 – 2010). Based on analysis of these maps and statistical assessment by using R application, the correlations between pH, temperature, and salinity are clarified. The results show that there are trends of decrease in pH, temperature and increase in salinity according to year. pH has good and significant correlations with water temperature and salinity in both simple and multiple linear regression.The results aim to provide a scientific reference for further research on water environment in this area.